2017
DOI: 10.1111/jocd.12355
|View full text |Cite
|
Sign up to set email alerts
|

Incubatory environment of the scalp impacts pre‐emergent hair to affect post‐emergent hair cuticle integrity

Abstract: SummaryObjectives: To determine whether the oxidative stress transmitted to newly grown hair from an unhealthy scalp has physical consequences to the cuticular condition and function.Methods: A uniquely designed 24-week clinical study included 8 weeks of pretreatment with a cosmetic shampoo and 16 weeks of treatment with either a potentiated zinc pyrithione (ZPT) antidandruff shampoo or a placebo cosmetic shampoo.This clinical design allowed the growth and acquisition of hair samples under conditions of varyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…On the other hand, El Hamd et al23 found that serum levels of MIF were significantly lower in patients with cutaneous warts compared to their healthy controls which could be explained by shift of MIF to the wart sites, a result which needs further research.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, El Hamd et al23 found that serum levels of MIF were significantly lower in patients with cutaneous warts compared to their healthy controls which could be explained by shift of MIF to the wart sites, a result which needs further research.…”
Section: Discussionmentioning
confidence: 95%
“…The protective benefits of the hair to the scalp, such as UVR screening, moisture retention, and mechanical shielding, are apparent, while the role of the scalp as an incubatory environment for the pre-emergent hair fiber is often disregarded. [41] However, there is a wealth of observational data on specific dermatological conditions of the scalp, such as dandruff and seborrheic dermatitis,[42434445464748] atopic dermatitis,[4449] and psoriasis,[50515253545556575859] providing the evidence for the role of the scalp condition in supporting the production of healthy hair. Again, oxidative stress is prevalent in all of these skin conditions,[60616263646566676869707172] just as in normal skin aging and related to the specific microbiome of the scalp and to the environmental exposures.…”
Section: Hair Fiber Quality Of Life From Scalp To Tipsmentioning
confidence: 99%
“…The protective benefits of the hair to the scalp, such as ultraviolet radiation (UVR) screening, moisture retention, and mechanical shielding, are obvious, while the role of the scalp as an incubatory environment for the preemergent hair fiber is often overlooked. [3]…”
Section: Introductionmentioning
confidence: 99%